Navigating the Discord: Assessing Civil-Military Relations Theory in Public Transparency Debate - Ghiffary Abdurrahman, Muhammad Kamil; Gultom, Yosua Saut Marulitua (Mandala: Jurnal Ilmu Hubungan Internasional, 2024)
Indonesia's government has faced significant criticism for its lack of transparency regarding defense and military expenditures. In early 2024, this issue garnered peak public attention when Prabowo Subianto, a key figure in Indonesia's military activities, defended the non-transparent approach as vital for securing regional strategic interests. This stance conflicts with the principles of liberal democracy, which prioritize public needs and aspirations. After reviewing existing literature, this paper finds that the Civil-Military Relations (CMR) theory has not yet been applied to assess the issue of military transparency at a domestic level. This study examines whether CMR theory can serve as an analytical framework for the discord between public demands for transparency towards military organizations. The findings suggest that while CMR theory is relevant to the relationship between civil and military and its justification for public demands for military transparency, the normative framework itself is inconsistent. Resonating with the existing literature, this paper also finds that this CMR is yet to be integrated with the corridor of political science and, thus best studied for practical and strategic needs; hence explains the requirement to assess more contextual and nuanced variables.